ANALYSIS OF THE INTERRELATION BETWEEN CONCEPT AND NOTION IN LINGUISTICS - Abdullayeva, Shahnoza (Educational Research in Universal Sciences, 2023)
This article analyzes the interrelation between notion and concept in linguistics. Also, it gives full definitions of the terms concept and notion, provides some samples from linguistic perspective, highlights the importance of culture in understanding the language. In the study of cognitive linguistics, a concept is a complex, multifaceted phenomenon that can be seen as a unit of memory. Linguocognitologists have defined and classed it in a variety of ways, resulting in a large number of variants and types. As for the term notion, it is an individual’s conception or impression something known, experienced, or imaged. It can be a theory or belief held by a person or group. Presentation of the information produced by synthesis, analogy, and comparison techniques.